The Wages Crisis in Australia What it is and what to do about it - Stewart, Andrew; Stanford, Jim; Hardy, Tess (University of Adelaide Press, 2018)
This edited volume of chapters resulted from an international conference held at the University of Adelaide in July 2016 under the same title to explore the multifaceted concept of ʿilm in Islam - its agency and manifestations in the connected realms of science, religion, and the arts. The aim is to explore the Islamic civilisational responses to major shifts in the concept of 'knowledge' that took place in the post-mediaeval period, and especially within the context of the 'early modern'. It asserts that the true value of knowledge lies in its cross-civilisational reach, as when the development of knowledge in pre-modern Islam exerted profound changes onto the Europeans, whose resurgence in the early modern period has in turn forced massive changes onto the Islamic worldview and its systems of knowledge. Now the landscape of knowledge has significantly changed, the Muslim mind, which has been historically calibrated to be particularly sensitive towards knowledge, can and should open to new horizons of knowing where science, religion, and art can meet again on freshly cultivated and intellectually fertile grounds.